BAWASLU Budgeting Mechanism on The Election of Regional Chiefs: Case Study of South Sulawesi - Dahliah, D. (Manunggal Halim Jaya, 2022)
The previous Pilkada, in terms of funding, the election of the regional head (Pilkada) was faced with two crucial things. First, holding regional elections budget. The second is the number of funds. The permit issued by the local government for the Pilkada itself will affect the area's fiscal space and development plans. The cost of holding the Pilkada comes from GDP, but the amount of the budget approved by the regional government varies depending on the financial capacity of each region. The first stage is the budget preparation stage in the budget cycle, which includes budget submissions from each section or department. The second stage is the budget approval stage. After the budget is ratified as law, all departments enter the budget implementation stage. The implementation of the budget must be accompanied by supervision to ensure that according to predetermined plans. The last stage is ratifying the budget calculation. The mechanism for managing the regional head election grants budget follows the laws and regulations regarding disbursement to reporting. However, from the results of the researcher's search, it was found that there are still things that need to be considered, especially in terms of financial transparency.